(untitled) (KYAMC Journal, 2020)
Background: Rehabilitation Medicine is the focal point on the refurbishment of the health and function, and reintegration of the patient into the community. Since inception, department of Physical Medicine and Rehabilitation (PMR) is dispensing state of the art services despite its fewer resources. Objective: To anticipate a brief recapitulation of the infrastructure of Rehabilitation medicine and its’ services as well as demographic data and, disease pattern among the patients dealt by it in a Tertiary Hospital. Materials and Methods: This is a retrospective study executed in the department of PMR of Kurmitola General Hospital, Dhaka from January 2019 to December 2019. Results: Currently 4 Rehabilitation Physicians (Physiatrist) and 3 Physical Therapists, are involved in indoor, outdoor and, specialized PMR services with 4 indoor beds. Total thirty four thousands seven hundred thirty six (n=34,736) patients were studied who received our services, among them 35.62% were male and 64.38% were female. 16% of patients were under 20 years of age, about 61% of patients belong to 2nd, 3rd, 4th, 5th decades and 23% were above 60 years of age. Nonspecific Low Back Pain (NSLBP) were 23.80%, 8.29% Neck pain, cervical spondylosis11.15%, lumbar spondylosis 11.52%, frozen shoulder 9.83%, PLID 7.39%, osteoarthritis 9.15%, facial palsy 0.53%, rheumatoid arthritis 4.47%, seronegative spondyloarthopathy 1.26%, Guillain-Barre` Syndrome (GBS) 0.15%, planter fasciitis 4.68%, 2.10 % postsurgical/post-traumatic stiffness and others were 5.13%. Conclusion: It is time demand to build more infrastructures country wide to improve physical medicine and rehabilitation services for the country people. KYAMC Journal Vol. 11, No.-2, July 2020, Page 62-66